2019
DOI: 10.1097/md.0000000000014414
|View full text |Cite
|
Sign up to set email alerts
|

Successful extracorporeal membrane oxygenation support for severe acute diquat and glyphosate poisoning

Abstract: Rationale: Because of the lack of an antidote or effective treatment, patients with severe acute diquat and glyphosate poisoning always died within a few hours. Extracorporeal membrane pulmonary oxygenation (ECMO), as an artificial heart-lung supporting system, can be applied to support lung that is expected to recover from reversible pathological damage. However, to our knowledge, the application of ECMO for patients with diquat and glyphosate poisoning has not been reported. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although more and more cases of health damage from GLY and preparations have been reported in recent years [10,11], there are still many different opinions on its toxicity [12]. The main divergences focus on two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Although more and more cases of health damage from GLY and preparations have been reported in recent years [10,11], there are still many different opinions on its toxicity [12]. The main divergences focus on two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to respiratory failure caused by diquat poisoning, one patient was successfully saved by venovenous extracorporeal membrane oxygenation (ECMO) 11 in a previous report. That patient had ingested about 100 mL of diquat (20 g per 100 mL) and 400 mL of glyphosate (41 g per 100 mL); this dose was much lower than that in our patient, and the previous patient vomited the herbicides soon after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…As a bridge to recovery from cardiopulmonary failure, ECMO can improve the survival rate of patients with refractory cardiogenic shock following poisoning [12][13][14] . Vardon [15] et al reported the successful rescue of patients with intractable ventricular arrhythmia and cardiogenic shock caused by severe yew poisoning using VA-ECMO.…”
Section: Discussionmentioning
confidence: 99%